Click, Measure, Succeed: A Bibliometric Journey and Emerging Research Gaps in Information Systems (IS) Effectiveness - Nor Asiah Taib; Izlawanie Muhammad; Suhaila Abdul Hamid (Global Academic Excellence (M) Sdn Bhd, 2026)
Tier 3- Indexed by MyCite